Piloting gender-oriented colorectal cancer screening with a faecal immunochemical test: population-based registry study from Finland - Sarkeala Tytti; Färkkilä Martti; Anttila Ahti; Hyöty Marja; Kairaluoma Matti; Rautio Tero; Voutilainen Markku; Helander Sanni; Jäntti Maija; Lehtinen Milla; Patrikka Lotta; Malila Nea; et al. (BMJ PUBLISHING GROUP, 2022)
Objective To assess the feasibility and evaluate the performance of a relaunched colorectal cancer (CRC) screening programme with different cut-offs for men and women.
Design Population-based registry study.
Setting Nine municipalities in Finland which started CRC screening with faecal immunochemical test (FIT) in April 2019 with cut-off levels 70 mu g Hg/g faeces for men and 25 mu g Hg/g faeces for women.
Participants Men (n=13 059) and women (n=14 669) aged 60-66 years invited to screening during the first programme year.
Outcome measures Participation rates, positivity rates, detection rates of CRC and advanced adenoma (AA), and positive predictive values (PPV) of FIT for CRC and AA.
Results Altogether 21 993 invitees returned stool samples. The participation rate of women (83.4%; 95% CI 82.8 to 84.0) was significantly higher than that of men (74.7%; 95% CI 73.9 to 75.4). The positivity rates were 2.4% (2.2 to 2.7) and 2.8% (2.5 to 3.1), respectively. In total, 37 CRCs and 116 AAs were detected. The detection rates of CRC and AA per 1000 participants were 1.8 (1.1 to 2.9) and 7.2 (5.6 to 9.1) for men and 1.6 (0.9 to 2.4) and 3.8 (2.8 to 5.0) for women. The PPVs per 100 positive tests were 6.6 (4.0 to 10.3) and 25.7 (20.6 to 31.4) for men and 6.4 (3.9 to 9.8) and 15.5 (11.6 to 20.2) for women.
Conclusions The chosen FIT strategy narrowed the gap in the diagnostic performance between men and women especially in the detection of CRC. The participation rates were excellent. The levels of positivity and detection rates were moderate and need further action. The results indicate that gender-specific protocols can be introduced to organised CRC screening. It is yet to be seen whether they are more effective than a uniform screening protocol.